ANALISIS DISTRIBUSI ZAKAT KONSUMTIF, ZAKAT PRODUKTIF DAN BANTUAN SOSIAL PANGAN (BSP) TERHADAP KEMISKINAN DI PROVINSI RIAU TAHUN 2019-2023 - Nuraini, Nuraini; Rosyetti, Rosyetti; Sidabalok, Supriani (Jurnal Daya Saing, 2025)
This research aims to analyze the distribution of consumptive zakat, productive zakat and food social assistance (BSP) on poverty in Riau Province in 2019-2023. The research used secondary data obtained from the Central Statistics Agency (BPS) of Riau Province, the Regional Office of the Ministry of Religion of Riau Province, Information Management Officials, the National Zakat Amil Agency of the Republic of Indonesia (PPID BAZNAS RI), and the National Zakat Amil Agency (BAZNAS) of Riau Province. The analysis method used is panel data regression and uses Eviews 12 software. The panel data used is 2019-2022 data as time series data and zakat and food social assistance (BSP) data in 12 districts/cities in Riau Province as cross section data. In this research, the distribution of consumptive zakat, productive zakat and social food assistance uses rupiah indicator data. The results of this research show that consumptive zakat, productive zakat and social food assistance simultaneously and significantly influence poverty in Riau Province in 2019-2023. The coefficient of determination (adjusted r-squared) is 0.995773, meaning that the independent variable can explain 99% of the dependent variable and the remaining 1% is explained by other variables outside this research. The probability value of the F statistic is 0.0000 <5%, which means that the independent variable simultaneously influences the dependent variable. Partially, consumptive zakat and productive zakat have a negative and significant effect of -0.356910 and -0.135952, food social assistance (BSP) has a positive and significant effect of 0.189355 on poverty in the districts/cities of Riau Province in 2019-2023